Capacity Building of Fish Processing Business Group By Sinjai Regency Fihseries Service South Sulawesi, Indonesia - Muhammad Yunus; Akmal Ibrahim; Syamsiah Hasyim (Indonesian Association for Public Administration (IAPA), 2018)
This study aims to find out and analyze the process of implementing capacity building for fish processing business groups by the Fisheries Service in Sinjai District. Data collection in this study is through interviews, and documentation. Data were analyzed using qualitative analysis. The results showed that in the process of implementing capacity building for fish business groups through training carried out by the Sinjai Regency Fisheries Office it had ineffective. There are several obstacles faced in the effort to develop the capacity of fish business groups, among others: Development participants have an unequal or heterogeneous background, such as education, work experience, and age. This will complicate and hamper the smoothness and implementation of training and education because of their catching power, perceptions, and reasoning for the lessons given differently. The curriculum that is established and taught is not in accordance with the needs of the trainees, in addition to the duration of the material delivery time is very short. In addition, the continuation of coaching is still lacking because after the training, it is not followed up by providing business capital as one of the problems faced by the group.